Perancangan Prototipe Sistem Informasi Pariwisata Berbasis Web di Kota Malang - Muhammad Efrizal Febriyan; Herdi Tri Nanda; Arafat Febriandirza (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2023)
One of the best tourism destinations in Indonesia is Malang. This city has a variety of uniqueness that can attract tourists to visit it. With the development of technology in this era, many make things easier, one of which is conveying information. This study aims to design a prototype of a web-based tourism information system in Malang City so that later tourists can more easily obtain information about this city. The method used is a descriptive method which will present and analyze facts systematically so that it will be easy to draw conclusions. Data collection was carried out by distributing questionnaires. In designing this prototype, Data Flow Diagrams, Flowcharts, Database Designs, and Output Designs will be designed. The results of this information system prototype will include various information about tourism in the city of Malang.